DETERMINANT MODEL OF CORPORATE DISCLOSURE SOCIAL RESPONSIBILITY - Sanjaya, Surya; Ammy, Baihaqi; Parlindungan, Ronni (RADJA PUBLIKA, 2021)
This research aims to find out the Effect of Company Size, Board of Commissioners Size, and Profitability on Corporate Social Responsibility Listed on the Indonesia Stock Exchange for the Period 2014-2018. This research approach uses an associative research approach. The method of data collection is done by means of data documentation sourced from the annual report of the Indonesia Stock Exchange. Based on the collection of samples conducted using the check list according to criteria, obtained the number of research samples as many as 6 companies from 15 populations. Research samples during the period 2014-2018 and data analysis techniques in this study are descriptive statistics, classical assumption tests that include normality tests, multicollinearity tests, and heteroskedity tests, multiple linear regression analysis, hypothesis testing which includes t test, f test and coefficient of determination. The results showed that the Size of the Company had a positive but insignificant effect on Corporate Social Responsibility Disclosure, the Size of the Board of Commissioners had a positive but insignificant effect on the disclosure of Corporate Social Responsibility, and Profitability had a positive but insignificant effect on the disclosure of Corporate Social Responsibility on Automotive companies listed on the Indonesia Stock Exchange for the period 2014-2018.